2021
DOI: 10.1063/5.0048802
|View full text |Cite
|
Sign up to set email alerts
|

Self-energized organic-inorganic hybrid composite for surface enhanced Raman spectroscopy

Abstract: In this study, we integrate plasmonic metal nanomaterials with a piezoelectric polyvinylidene fluoride (PVDF) polymer and lithium niobate (LiNbO 3 ) based composite to form an all-solid-state flexible self-energized sensor. We demonstrate that following the application of a load, the film enhances the surface-enhanced Raman spectroscopy (SERS) signal of an analyte molecule up to 14 times. The piezoelectric β-phase of PVDF in the film is optimized through the introduction of multi-walled carbon nanotubes and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Recently flexible polymer-based (PDMS 108 , PMMA 109 , PET 110 , PVDF 111,112 etc.) SERS substrates have gained interest from various research groups.…”
Section: -11mentioning
confidence: 99%
“…Recently flexible polymer-based (PDMS 108 , PMMA 109 , PET 110 , PVDF 111,112 etc.) SERS substrates have gained interest from various research groups.…”
Section: -11mentioning
confidence: 99%
“…James H. Rice et al developed a PVDF/LiNbO3 piezoelectric film. [ 40 ] It is believed that the charge generated by the applied mechanical stress can be transferred to the analyte molecules, resulting in an enhanced CM mechanism.…”
Section: Recent Advances Of E‐sersmentioning
confidence: 99%
“…It has been shown that adding reduced graphene oxide (rGO) and multiwall carbon nanotubes (MWCNTs) to PVDF polymer boosts the β-phase of piezoelectricity. 25 Li et al developed a self-energized E-SERS substrate using PVDF with reduced graphene oxide along with silver nanowires (Ag NWs). 26 They observed modulation of the signal up to 10 times for probe molecules via electrical energy transfer to plasmonic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric polymers filled with 2D material can also be used to strengthen the SERS signal by modifying the electroactive polar phase. It has been shown that adding reduced graphene oxide (rGO) and multiwall carbon nanotubes (MWCNTs) to PVDF polymer boosts the β-phase of piezoelectricity . Li et al developed a self-energized E-SERS substrate using PVDF with reduced graphene oxide along with silver nanowires (Ag NWs) .…”
Section: Introductionmentioning
confidence: 99%